Unlocking Nurse Satisfaction Global Imperatives for Retention and Wellbeing: Mengungkap Kepuasan Perawat Imperatif Global untuk Retensi dan Kesejahteraan - Hassan Mohammed Hassan; Faraj Faraj (Academia Open, 2024)
This study explores job satisfaction among nurses through a descriptive cross-sectional analysis conducted from January to April 2024, using a purposive sample of 400 participants. The findings reveal that while 85.9% of nurses are moderately satisfied with their jobs, satisfaction varies significantly between internal job elements (77.5% satisfaction) and external job factors (62.2% satisfaction). The study recommends the implementation of career development programs, recognition initiatives, and work-life balance strategies, alongside stress management and resilience training, to enhance overall job satisfaction and prevent burnout. These measures are crucial for improving healthcare outcomes and reducing staff turnover. Highlights: Moderate Satisfaction: Most nurses are moderately satisfied, highlighting areas for improvement. Satisfaction Disparity: There's a significant gap between satisfaction with internal and external job elements. Strategic Interventions: Career development and stress management programs are recommended to boost satisfaction and retention. Keywords: Nurse Satisfaction, Job Factors, Healthcare Management, Stress Prevention, Workforce Stability